A longitudinal study on clinical diseases and disorders of cattle and goats in Sylhet, Bangladesh (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The objective of this research work was to find out the prevalence of clinically occurring diseases and the disorders in cattle and goats at the Sylhet Agricultural University area, Sylhet during January to December 2013. Materials and methods: This clinical study was carried out on 775 clinical cases (553 cattle and 222 goats) based on the general, clinical, physical and microscopical examination along with common laboratory techniques. Results: The clinically observed cases in cattle were (i) gyneco-obstetrical (15.37%; n=85/553; P=0.038), (ii) metabolic and nutritional (9.94%; n=55/553; P=0.245), (iii) bacterial and viral (26.22%; n=145/553; P=